Systemic drugs that influence titanium implant osseointegration. (2nd January 2017) - Apostu, Dragos; Lucaciu, Ondine; Lucaciu, Gheorghe Dan Osvald; Crisan, Bogdan; Crisan, Liana; Baciut, Mihaela; Onisor, Florin; Baciut, Grigore; Câmpian, Radu Septimiu; Bran, Simion
Abstract: Titanium implants are widely used on an increasing number of patients in orthopedic and dental medicine. Despite the good survival rates of these implants, failures that lead to important socio-economic consequences still exist. Recently, research aimed at improving implant fixation, a process called osseointegration, has focused on a new, innovative field: systemic delivery of drugs. Following implant fixation, patients receive systemic drugs that could either impair or enhance osseointegration; these drugs include anabolic and anti-catabolic bone-acting agents in addition to new treatments. Anabolic bone-acting agents include parathyroid hormone (PTH) peptides, simvastatin, prostaglandin EP4 receptor antagonist, vitamin D and strontium ranelate; anti-catabolic bone-acting agents include compounds like calcitonin, biphosphonates, RANK/RANKL/OPG system and selective estrogen receptor modulators (SERM). Examples of the new therapies include DKK1- and anti-sclerostin antibodies. All classes of treatments have proven to possess positive impacts such as an increase in bone mineral density and on osseointegration. In order to prevent complications from occurring after surgery, some post-operative systemic drugs are administered; these can show an impairment in the osseointegration process. These include nonsteroidal anti-inflammatory drugs, proton pump inhibitors and selective serotonin reuptake inhibitors. The effects of aspirin, acetaminophen, opioids, adjuvants, anticoagulants and antibiotics in implant fixations are not fully understood, but studies are being carried out to investigate potential ramifications. It is currently accepted that systemic pharmacological agents can either enhance or impair implant osseointegration; therefore, proper drug selection is essential. This review aims to discuss the varying effects of three different classes of treatments on improving this process.